Individual Criminal Liability and Collective Civil Responsibility: Do They Reinforce or Contradict One Another? - Thomas M. Franck (Washington University Global Studies Law Review, 2007)
Does the ICJ, in discharging its responsibility under Article IX to establish the “responsibility” of a state for genocide, risk trenching on the jurisdiction now assigned to the ICTY and ICC? And does it risk perpetuating a notion of “collective guilt”?
Keywords: Genocide; Criminal liability; Collective guilt; Government liability